Potentielle køretidsgevinster ved anvendelse af togsæt med elektrisk traktion frem for togsæt med dieseltraktion - Petersen, Jakob Møldrup; Fick, Karsten (Proceedings from the Annual Transport Conference at Aalborg University, 2011)
As part of a study about the effects of further electrification in Denmark, the need arose to find some precise figures for the saving in running time on a given line, when converting diesel traction to electric traction. A neutral comparison of this, was not located, so with assistance from Bombardier, we decided to make a number of runtime calculations on Danish infrastructure, using either a diesel ITINO or an electric Talent 2. The models in the train families were chosen to have two trains that was very comparable. The two traction/speed curves can be seen below. Red for diesel, Green for electric. The calculations show that in the Danish regional/IC traffic, there is a saving potential in travelling time in the area of 5 – 10%. The saving potential is widely dependent on the type of operation and the infrastructure – operation with many stops while still being able to reach max speed in between stops naturally has the most potential. The potential saving in runtime per station stop is around 35 seconds.